Analisis Fungsi Pengawasan Inspektorat Sebagai Aparat Pengawas Intern Pemerintah (APIP) dan Komitmen Organisasi Terhadap Kinerja Perangkat Daerah di Pemerintah Daerah Provinsi Sulawesi Utara - Takaendengan, Dormina (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
The result of the research shows that partially supervision has significant effect on the Performance of Regional Device in Local Government of North Sulawesi. Organizational Commitment is partially significant to the performance of regional apparatus in North Sulawesi Local Government. Monitoring and Organizational Commitment have significant effect simultaneously on Local Device Performance in Local Government of North Sulawesi.Keywords: Monitoring, Organizational Commitment, Performance